Impact of Immune Response on Outcomes in Hepatocellular Carcinoma: Association With Vascular Formation. Issue 6 (20th October 2020) - Itoh, Shinji; Yoshizumi, Tomoharu; Yugawa, Kyohei; Imai, Daisuke; Yoshiya, Shohei; Takeishi, Kazuki; Toshima, Takeo; Harada, Noboru; Ikegami, Toru; Soejima, Yuji; Kohashi, Kenichi; Oda, Yoshinao; et al.
Abstract : Background and Aims: We investigated the prognostic value of programmed death ligand 1 (PD‐L1) expression, tumor‐infiltrating CD8‐positive T‐cell status, and their combination in hepatocellular carcinoma (HCC). Their association with PD‐L1 expression and vascular formation was further explored. Approach and Results: Using a database of 387 patients who underwent hepatic resection for HCC, immunohistochemical staining of PD‐L1, CD8, and CD34 was performed. Additionally, we undertook an enzyme‐linked immunosorbent assay for soluble PD‐L1. Compared with patients with HCC and PD‐L1–negative expression (n = 311), patients with HCC and PD‐L1–positive expression (n = 76) showed significantly worse overall survival (OS; multivariate hazard ratio, 2.502; 95% confidence interval [CI], 1.716‐3.649; P < 0.0001). The presence of tumor‐infiltrating CD8‐positive T cells was significantly correlated with longer OS (multivariate hazard ratio, 0.383; 95% CI, 0.274‐0.537; P < 0.0001). Stratification based on PD‐L1 expression in cancer cells and tumor‐infiltrating CD8‐positive T‐cell status was also significantly associated with OS (log‐rank, P < 0.0001). HCC with PD‐L1–positive expression was significantly correlated with positivity for vessels that encapsulated tumor clusters. Serum PD‐L1 levels were significantly higher in the group of patients who had PD‐L1–positive expression than in the group of patients who had PD‐L1–negative expression ( P = 0.0158). Conclusions: PD‐L1 expression in cancer cells was associated with a poor clinical outcome and vascular formation in patients with HCC. Additionally, the combination of PD‐L1 expression with tumor‐infiltrating CD8‐positive T‐cell status enabled further classification of patients based on their clinical outcome. Thus, PD‐L1 expression in cancer cells and tumor‐infiltrating CD8‐positive T‐cell status might serve as predictive tissue biomarkers.